Evaluation of impact assessment of mining-industrial development in central part of Iran; Case study :Chadormalloo Complex Impact on Bahabad County - dr. seyed mahmood mir abolghasemi behabadi (جغرافیا و آمایش شهری منطقه‌ای, 2019)
Nowadays, impacts of developmental measures on social, economic, environmental and physical dimensions is one of the important factors in the success or failure of developmental measures and development patterns. In this regard comprehensive assessments of impacts is essential. In other words, a comprehensive assessment of the effects of developmental measures and development patterns will allow us to fully assess the effects and achieve the model of the impact of industrial-mineral facilities. In this regard, the present study is based on a comprehensive impact assessment approach and a review of the impacts of the Chadermulu mine on the city of Bahabad in the search for a model of the impact of mineral-industrial centers on the settlements in the central regions of Iran. From the perspective of the nature of this research, it is a descriptive-analytical method that by collecting documentation, library and survey methods, collecting the information needed for research and then using T-test and path analyses to analysis the information has taken place. The results of the research show that the negative effects were higher in socio-cultural indicators and then the environmental indicators, and in the economic and physical indicators of the Chadormalloo complex there were more positive effects. The experience of mineral-industrial development in Central Iran, and especially in Bahabad, shows that although this model is relatively successful from the economic point of view and at the provincial and national levels, but from the perspective of the local economy, the environment as well as the socio-cultural areas with many negative impacts And has been challenging the issue of sustainable development at local scale. On the local scale, in contrast to what has been lost, there is no real and desirable results that can be described as "the sustainable and important role of mineral-industrial development in the process of developing central Iran", and unfortunately it should be considered as "legacy" Indemnified Mineral-Industrial Development on the Process of Destruction of Central Iranian Settlements.